English for everyone. Course book. Level 1 beginner - Harding, Rachel; Barduhn, Susan; Bowen, Tim (London Dk Publishing, 2016)
Summary/Review: "Level 1 of a complete self-study English-language course that combines easy-to-use visual learning with crystal-clear grammar explanations, practice exercises, and free audio."--from page 4 of cover
13
Keywords: English language -- Programmed instruction; English language -- Self-instruction; English language -- Terms and phrases; English language -- Textbooks for foreign speakers